(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The word empowerment is characterized as the procedure by which women take control and responsibility for decisions. Empowerment is a procedure of awareness and limit building prompting more noteworthy participation, to more noteworthy decision making power and control and transformative activity. Empowerment of women implies tackling women power by conscientising their tremendous potential and urging them to work towards achieving a stately and fulfilling lifestyle through confidence and skill as individual with self-respect, rights and responsibilities. The center elements of empowerment have been characterized as office (the capacity to characterize one’s objectives and follow up on them), awareness of gendered power structures, self-regard, and self-confidence.